Augmented Reality as E-learning Tool in Primary Schools’ Education: Barriers to Teachers’ Adoption - Alkhattabi, Mona (International journal of emerging technologies in learning, 2017)
Today, primary school teachers face challenges when dealing with digital natives. As a result of the explosion and rapid growth in information technologies that can be used in education, there are increasing demands to adopt technology in education, in order to influence students to learn actively and motivate them to gain an effective learning process. Augmented reality applications show good potential in giving students more active, effective and meaningful learning processes. Moreover, augmented reality attracts research attention for its ability to allow students to be immersed in realistic experiences. Therefore, this study reviews the main benefits of using augmented reality applications in education. It also aims to examine user acceptance of augmented reality applications within an e-learning environment in primary schools, from the teachers’ perspective, as an initial experiment. Moreover, it explores the main barriers and benefits when adopting this technology.